Characterization and reactivity of charcoal from high temperature pyrolysis (800–1600 °C). (1st January 2019) - Surup, Gerrit Ralf; Nielsen, Henrik Kofoed; Heidelmann, Markus; Anna Trubetskaya,
Highlights: Biomass char samples were generated in slow pyrolysis at high-temperatures. The char reactivity was determined in 20 and 100 vol. The CO2 concentration had the highest influence on char reactivity. The oak char from 1600 °C pyrolysis showed the most ordered structure. Both spruce and oak chars showed a structure of non-graphitizing carbons. Abstract: This study presents the effect of wood origin and heat treatment temperature on the CO2 reactivity, nanostructure and carbon chemistry of chars prepared at 800, 1200, and 1600 °C in slow pyrolysis reactors. The structure of charcoal was characterized by transmission electron microscopy, Raman spectroscopy, mercury intrusion porosimetry and N2 adsorption. The CO2 reactivity of char was investigated by thermogravimetric analysis. Results showed that spruce and oak chars have similar reactivity at all heat treatment temperatures. The oak char prepared at 1600 °C contained long and flat graphene layers and interplanar distance that is similar to graphite and thus, was more ordered than the spruce char. The TEM analysis showed that charcoal had structural characteristics of non-graphitizing carbon. Thus, increasing heat treatment temperature increases the graphitization of char structure, leading to the reactivity that is nearly similar to that of low reactive metallurgical coke. The wood origin, heat treatment temperature, nanostructure, differences in porosity and pore size of char influenced the CO2 reactivity less than the differences in CO2 concentrations.